Haldhi Dhoodh (Turmeric Milk) - Khan, Eman (Stimulus: A Medical Humanities Journal, 2023)
This poem depicts chronic illness and lost time. It's also expressive of the unique way Disability is viewed in the South Asian community and how turmeric milk is seen as a cure for many ailments. It's a poem that leads to accepting that turmeric milk isn't a cure for a systemic illness.